Handbook of Ecological Indicators for Assessment of Ecosystem Health - Jorgensen, Sven (CRC Press, 2009)
The field of ecosystem health explores the interactions between natural systems, human health, and social organization. Handbook of Ecological Indicators for Assessment of Ecosystem Health is the first comprehensive account of ecological indicators for evaluating the health of a wide variety of ecosystems. It presents a conceptual framework for selecting, evaluating and validating ecological indicators of ecosystem health and applies this framework in a series of chapters on major ecosystem types, including coastal areas, forests, wetlands, fisheries and agricultural land. This text will be useful for a wide range of professionals, including those in government agencies worldwide.